Specific features of the clinical picture, diagnosis, and treatment of trophoblastic tumor of the placental bed - D. A. Lisaev; B. O. Toloknov; E. E. Makhova; T. I. Zakharova; I. V. Markina (ABV-press, 2014)
Trophoblastic tumor of the placental bed is a highly malignant form of trophoblastic disease that occurs extremely rarely: 0.4-2% of all the trophoblastic tumors. In the world literature, there are reports on about 200 cases of this disease. The tumor occurs at a repro- ductive age (median age 30 years), occasionally even long after pregnancy, which makes the problem of diagnosis and treatment of the pathology particularly pressing. In 30% of cases, there are metastases more frequently to the lung and vagina. The diagnostic features of a placental bed tumor include the low serum levels of chorionic gonadotropin β-subunits and the higher level of human placental lactogen. Due to low tumor susceptibility to chemotherapy, the patients should undergo surgical intervention as uterine extirpation at the first treatment stage, which is followed by chemotherapy.